Alternativas de diversificación internacional para portafolios de acciones de la Bolsa de Valores de Lima - Ames Santillán, Juan Carlos (2012)
This paper gives an estimation of efficient frontiers for investment portfolios, they include stocks from Lima Stock Exchange General Index, Dow Jones Industrial Average, Gold, Cooper, Fixed Income Instruments of Peruvian government and savings in Peruvian financial institutions. The paper concludes that risk of investment in local portfolio reduces as a consequence of diversification, gold is an important asset and contributes to reduce portfolio risk.